ANALISIS SUPPLY CHAIN MANAGEMENT PADA PT. MONIER DI SIDOARJO - Moh Afrizal Miradji (BALANCE: Economic, Business, Management and Accounting Journal, 2014)
Supply     Chain     Management     covers     all    the     activities     since material   came   from   the   supplier,   then   the   material   was   processed   into semi-finished  products  or  finished  products  until  the  product  is distributed  to consumers. To know the performance of the company's Supply Chain, measurement is needed. From these measurements  will be obtained result, so good or not good performance of the company's Supply Chain can be seen and can  find  the  weaknesses  of  existing  systems  to  be  repaired.  Given  a  good supply chain performance, the performance the company will increasingly focus and provide benefits, whether for the company, suppliers, and consumers. This study used qualitative data. The scope of analysis in this research is related to supply chain management  functions in PT Monier Sidoarjo, in the implementation of financial and operational audits. Source data is data obtained directly by the author in the research by conducting  surveys and meetings as well as direct interviews with relevant parties. Research findings stating that in terms of financial, SCM can then be to increase  profits  at the  company,  but  companies  need  to conduct  operational checks on the production function, attention and immediate action to factors that cause a lack of efficiency and effectiveness of the production function is the lack of communication  between  the sales and production,  delays  in receiving  raw materials,  production  planning  and  scheduling  patterns.  Companies  need  to perform the separation function explicitly against a concurrently-a  concurrently functions, provide either a separate storage area for raw materials, intermediate goods   and   production   results,   and   conduct   internal   documents   that   are supposed  to  exist  in  order  to  improve  the  internal  control  system  and  can provide adequate protection against corporate wealth Organizations need to separate